1970
DOI: 10.1136/gut.11.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Familial polyposis coli associated with extracolonic abnormalities

Abstract: SUMMARY The pedigree of a polyposis coli family, in which several individuals had extracolonic abnormalities associated with the condition, is presented. Some of the problems encountered in management are discussed. The literature is reviewed and a simple classification ofthe extracolonic abnormalities is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The precise differentiation of the latter two groups may be impossible on both clinical and pathological grounds. In Gardner's syndrome there have been two reports of duodenal carcinoma one of which, like the case here described, presented with duodenal obstruction (Parks et al, 1970;Muir et al, 1967). A further seven cases with peri-ampullary malignancy have been recorded.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The precise differentiation of the latter two groups may be impossible on both clinical and pathological grounds. In Gardner's syndrome there have been two reports of duodenal carcinoma one of which, like the case here described, presented with duodenal obstruction (Parks et al, 1970;Muir et al, 1967). A further seven cases with peri-ampullary malignancy have been recorded.…”
Section: Discussionsupporting
confidence: 50%
“…Today many more extra-colonic associations have been described with ACR, the best known being the occurrence of multiple epidermoid cysts, soft tissue tumours of the skin and osteomata of the skull and mandible, given the eponym 'Gardner's syndrome' after Gardner and Richard's publication in 1953. Various reports have been made in the literature of duodenal polyps, duodenal carcinoma, and peri-ampullary malignancy in association with Gardner's syndrome and ACR (MacDonald et al, 1967;McFarland, Scheetz and Knisley, 1968;Parks, Bussey and Lockhart-Mummery, 1970; Capps, Lewis and Gazzaniga, 1968;Muir, Bell and Barlow, 1967;Melmed and Bouchier, 1972;Mir-Madjlessi et al, 1973. The pathological involvement can be classified into three main groups; (a) the occurrence of duodenal polyps, (b) duodenal carcinoma which may be multicentric and (c) peri-ampullary carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Early proponents of upper gastrointestinal surveillance suggested that FAP patients should undergo regular barium radiology [87][88][89], but radiological assessment does not provide any histological samples and is likely to result in an inaccurate assessment of malignant potential. The first systematic large scale endoscopic series characterised disease distribution more completely ( Figure 1) and led the authors to propose sequential endoscopy and biopsy as part of a surveillance programme [35,47].…”
Section: Surveillance Of the Upper Gastrointestinal Tractmentioning
confidence: 99%
“…Therefore the mode of inheritance is considered to be autosomal recessive. On the other hand, in the cases of Camiel et al (1968), Capps et al (1968 and Parks et al (1970) brain tumour developed together with colonic polyposis within the wellconfirmed pedigrees of familial polyposis coli. As they include many patients suffering from colonic polyposis, but as no one else in the family has brain tumour, association of brain tumour with colonic polyposis in these three patients seems to be coincidental.…”
Section: Discussionmentioning
confidence: 88%